Menyikapi Budaya Kekerasan - Zaenul Mahmudi (el Harakah: Jurnal Budaya Islam, 2002)
Violence that occurred during the reign of Abdurrahman Wahid, whether nuanced, religion, race and intergroup (SARA) or nuanced disintegration of the nation can not be seen from the side lahiriyah, but the violence needs to be studied in depth from various aspects which surrounds it, as Abdurrahman Wahid's rise as president is a national compromise reflected in his cabinet structure that seeks to accommodate the aspirations of all political contestants who participate in the elections, so the cabinet is called the "National Unity" cabinet. This has led to the emergence of leadership dualism from his cabinet ministers, under certain conditions to his political party and in other conditions to the President. And more exacerbating, the rise of Abdurrahman Wahid inherited the condition of 'doomsday' in all its fields as the legacy of the New Order regime under the leadership of General Soeharto. In this paper the authors will examine the violence that occurred during the reign of Abdurrahman Wahid from various aspects. In addition the author offers several solutions from Islamic perspective. Kekerasan-kekerasan yang terjadi pada masa Pemerintahan Abdurrahman Wahid, baik yang bernuansa Suku, Agama, Ras dan Antar Golongan (SARA) maupun yang bernuansa disintegrasi bangsa tidak bisa dilihat dari sisi lahiriyah saja, tetapi kekerasan-kekerasan tersebut perlu dikaji secara mendalam dari berbagai aspek yang melingkupinya, karena naiknya Abdurrahman Wahid sebagai presiden merupakan suatu kompromi nasional yang tercermin dalam susunan kabinetnya yang berusaha mewadahi aspirasi dari semua kontestan politik yang ikut pemilu, sehingga kabinet tersebut dinamakan kabinet "Persatuan Nasional". Hal ini berimbas kepada munculnya dualisme kepemimpinan dari para menteri kabinetnya, dalam kondisi tertentu kepada parpolnya dan dalam kondisi yang lain kepada Presiden. Dan yang lebih memperparah, naiknya Abdurrahman Wahid mewarisi kondisi 'kiamat' dalam segala bidangnya sebagai warisan rezim Orde Baru di bawah pimpinan Jendral Soeharto. Dalam tulisan ini penulis akan mengkaji kekerasan-kekerasan yang terjadi pada masa Pemerintahan Abdurrahman Wahid dari berbagai aspek. Selain itu penulis menawarkan beberapa solusi dari perspektif Islam.